2020
DOI: 10.1002/mnfr.201900873
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐ and Fish‐Derived n‐3 PUFAs Suppress Citrobacter Rodentium–Induced Colonic Inflammation

Abstract: Scope Marine‐derived n‐3 PUFAs may ameliorate inflammation associated with inflammatory bowel diseases. Plant‐derived n‐3 PUFAs are thought to be inferior owing to shorter chain lengths. The aim of this study is to compare the impact of plant‐ and fish‐derived PUFAs on murine colitis. Methods and results C57BL/6 mice are fed high fat (36% kcal) diets with either 2.5% w/w sunflower oil (SO), flaxseed oil (FSO), ahiflower oil (AO), or fish oil (FO). After 4 weeks, mice are orogastrically challenged with Citrobac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 51 publications
(80 reference statements)
0
9
0
Order By: Relevance
“…Manipulation of lipid content in host tissues, including omega-6 PUFAs such as arachidonic acid (C 20:4 ) and omega-3 PUFAs such as alpha-linoleic acid (C 18:3 ), eicosapentaenoic acid (C 20:5 ), and docosahexaenoic acid (C 22:6 ), through dietary, genetic, or pharmacological interventions is associated with altered severity of disease in numerous experimental models of colitis (55,56). In the context of enteric bacterial infection, the administration of different dietary oil supplements can alter disease outcomes in mice challenged with Citrobacter rodentium, a murine pathogen that serves as an established model for human EHEC and enteropathogenic E. coli (EPEC) infection (57)(58)(59)(60)(61). Given the high fat content and increased omega-6-to-omega-3 ratios characteristic of the Western diet, there is much interest in defining the molecular mechanisms by which specific PUFAs may modulate the outcomes of intestinal diseases such as enteric infection.…”
Section: Discussionmentioning
confidence: 99%
“…Manipulation of lipid content in host tissues, including omega-6 PUFAs such as arachidonic acid (C 20:4 ) and omega-3 PUFAs such as alpha-linoleic acid (C 18:3 ), eicosapentaenoic acid (C 20:5 ), and docosahexaenoic acid (C 22:6 ), through dietary, genetic, or pharmacological interventions is associated with altered severity of disease in numerous experimental models of colitis (55,56). In the context of enteric bacterial infection, the administration of different dietary oil supplements can alter disease outcomes in mice challenged with Citrobacter rodentium, a murine pathogen that serves as an established model for human EHEC and enteropathogenic E. coli (EPEC) infection (57)(58)(59)(60)(61). Given the high fat content and increased omega-6-to-omega-3 ratios characteristic of the Western diet, there is much interest in defining the molecular mechanisms by which specific PUFAs may modulate the outcomes of intestinal diseases such as enteric infection.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, the protective effect of n-3 FAs has been correlated with the decreased production of pro-inflammatory cytokines, through decreased alkaline phosphatase and bile duct injury. However, clinical trials addressing the benefit of n-3- PUFAs in IBD have yielded mixed results, with benefits differing based on the source of PUFA, suggesting differences in antiinflammatory activity between marine-derived n-3-PUFAS are superior to that derived from plants (48). Addressing the effectiveness of n-3-PUFAs has largely focused on marinederived fish oils on the notion that they provide EPA and DHA, whereas plant-derived n-3-PUFAs ALA and stearidonic acid are inefficiently converted to long-chain bioactive forms (49).…”
Section: Overall Fatty Acid Effect On Inflammation Is Variablementioning
confidence: 99%
“…Further, different FAs can exert the same antiinflammatory activity via different mechanisms. For instance, in C.Rodentium-colitis mice, supplementation with either fish or plant oil (flaxseed, ahiflower or sunflower) attenuated colitis, however fish oil reduced lipoxin and leukotriene B4 levels, whereas plant oils increased pro-resolving mediators D, E and T-series resolvins (48). The FA structure is also pivotal in disease outcome.…”
Section: Factors That Alter the Effect Of Fatty Acids (Pro Vs Anti-inflammatory)mentioning
confidence: 99%
“…In contrast, no effect on the peroxisome proliferator-activated receptor y (PPAR-γ) activation was observed ( 66 ). Some studies have observed exacerbating effects of flaxseed oil (being rich in C18:3n-3) on colitis in C. rodentium challenged mice despite increased n-3 PUFAs in intestinal tissues and increased caecal concentration of SCFAs (with proposed anti-inflammatory effects) ( 67 ). Other studies on plant oils have revealed that when mother rats during gestation and lactation were fed a diet high in safflower oil (around 72% C18:2n-6) compared to those fed diets high in canola oil (C18:3n-3) or high in oleic safflower oil (C18:1n-9), off-springs had more severe colitis ( 68 ).…”
Section: Plant-derived Fatty Acidsmentioning
confidence: 99%